USM LAUDS MOHE’s PLAN TO SET UP A NATIONAL REGISTRY FOR PhD HOLDERS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, November 2016 – Universiti Sains Malaysia (USM) has applauded the Ministry of Higher Education (MoHE) recent decision to set up a National Doctor of Philosophy (PhD) Registry to curb the production and usage of fraudulent academic titles by individuals and organisations.